Martian Proton Aurora Brightening Reveals Atmospheric Ion Loss Intensifying. Issue 5 (7th March 2023) - He, Fei; Fan, Kai; Hughes, Andréa; Wei, Yong; Cui, Jun; Schneider, Nicholas; Fraenz, Markus; Yao, Zhonghua; Rong, Zhaojin; Chai, Lihui; Yan, Limei; Wu, Shi‐Qi; et al.
Abstract: The Martian proton aurora is a distinct aurora phenomenon resulting from the direct deposition of solar wind energy into Mars' dayside atmosphere. What solar wind parameters influence the aurora activity in the short term is yet unknown, as are the associated repercussions in the Martian atmospheric ion loss. Here we present observational evidence of synchronized proton aurora brightening and atmospheric ion loss intensifying on Mars, controlled by solar wind dynamic pressure, using observations by the Mars Atmosphere and Volatile Evolution spacecraft. The solar wind dynamic pressure possibly has a saturation effect on brightening proton aurora. Significant erosion of the Martian ionosphere during periods of high dynamic pressure indicates at least five‐to‐tenfold increase in atmospheric ion loss. An empirical relationship between ion escape rate and auroral emission enhancement is established, providing a new proxy of Mars' atmospheric ion loss with optical imaging that may be used remotely and with greater flexibility. Plain Language Summary: Ion loss during solar events early in Mars history may have been the major cause to the long‐term evolution of the Mars atmosphere. Restricted by observation data, the relationship between ion loss and solar wind is still in debate. We have shown observational evidence for synchronized dayside proton aurora brightening and atmospheric ion loss intensifying on Mars, controlled by solar wind dynamic pressure using comprehensive observations by the NASA's MAVEN spacecraft. A power law model between ion escape rate and proton auroral emission enhancement is established for the first time, providing a new proxy of Mars' atmospheric loss with optical imaging that may be used remotely and with greater flexibility. The results presented in this study shed light on the direct control of dynamic pressure on interactions of the solar wind with Mars and other objects in solar system (e.g., Venus and Titan), and presumably stellar wind with exoplanets. Key Points: Synchronized proton aurora brightening and atmospheric ion loss intensifying on Mars, both controlled by solar wind dynamic pressure The solar wind dynamic pressure possibly has a saturation effect on brightening proton aurora An empirical power law model between ion escape rate and proton auroral emission enhancement is established